Transport Nutrien penyebab Eutrofikasi dari Daerah Tangkapan Air Waduk Mrica Banjarnegara - Agatha Sih Piranti; Soedarmadji Soedarmadji; Gentur Waluyo; Suwardi Suwardi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
The transport of nutrien causing eutrophication in water from catchment area especially fosforus (P) through runoff is determined by type of landuses, slop, soils type, and land cover (Jeje,2006) . The research was conducted using a survey method. The sampling technique was done by a purposive sampling on any flooding in the rivers that pass through areas with specific land use (settlement, forest, plantations, agricultural fields and rice field). The main parameters were river discharge and the content of nutrients causing eutrophication that was phosphorus (P) in rivers. The P loadingfrom cacthment area to Mrica reservoir was 11,526,706.14 kg/year and the load allocation (LA) was 3,833,587.70 kg/year. The reservoir operational of power generating dan flushing activity were able to manage the LA up to 1,147,329.09kg/year, so the TMDL of Mrica reservoir become 4,980,916.78kg/year. It was concluded that the highest transport of P was from paddy field and then followed by respectivelly agricultural (potato) field, plantation (perhutani) field, settlement area, and forest area.